Lonicerae Japonicae Flos Extract Promotes Sleep in Sleep-Deprived and Lipopolysaccharide-Challenged Mice - Hua, Ruifang; Ding, Yan; Liu, Xiaolong; Niu, Bingxuan; Chen, Xinfeng; Zhang, Jingjing; Liu, Kerui; Yang, Pei; Zhu, Xiaofei; Xue, Jintao; Wang, Hui (Frontiers in Neuroscience, 2022)
Lonicerae Japonicae Flos (LJF) is commonly used in Chinese herbal medicines and exhibits anti-viral, anti-oxidative, and anti-inflammatory properties. The reciprocal relationship between sleep, the immune system and the central nervous system is well-established in the animal models. In this study, we used the mouse model to analyze the beneficial effects of the LJF on the dysregulated sleep-wakefulness cycle in response to acute sleep deprivation and lipopolysaccharide (LPS)-induced inflammation and the potential underlying mechanisms. Polysomnography data showed that LJF increased the time spent in non-rapid eye movement (NREM) sleep during the day under basal conditions. Furthermore, latency to sleep was reduced and the time spent in rapid eye movement (REM) sleep was increased during recovery from acute sleep deprivation. Furthermore, LJF-treated mice showed increased REM sleep and altered electroencephalogram (EEG) power spectrum in response to intra-peritoneal injection of LPS. LJF significantly reduced the levels of proinflammatory cytokines such as IL-6, TNF-α, and IL-1β in the blood serum as well as hippocampus, and medial prefrontal cortex (mPFC) tissues in the LPS-challenged mice by inhibiting microglial activation. Moreover, LJF increased the time spent in REM sleep in the LPS-challenged mice compared to the control mice. These results suggested that LJF stimulated the sleep drive in response to acute sleep deprivation and LPS-induced inflammation, thereby increasing REM sleep for recovery and neuroprotection. In conclusion, our findings demonstrate that the clinical potential of LJF in treating sleep disorders related to sleep deprivation and neuro-inflammation.